Formoterol reduces muscle wasting in mice undergoing doxorubicin chemotherapy - Lima Junior, Edson Alves de; Teixeira, Alexandre Abilio de Souza; Silveira, Loreana Sanches; Jové, Queralt; Ladrón, Natalia Álvarez; Pereira, Marcelo G.; López-Soriano, Francisco Javier; Argilés, Josep M.; Brum, Patrícia Chakur; Busquets, Silvia; Neto, José Cesar Rosa (Frontiers in Oncology, 2024)
Background: Even though doxorubicin (DOX) chemotherapy promotes intense muscle wasting, this drug is still widely used in clinical practice due to its remarkable efficiency in managing cancer. On the other hand, intense muscle loss during the oncologic treatment is considered a bad prognosis for the disease's evolution and the patient's quality of life. In this sense, strategies that can counteract the muscle wasting induced by DOX are essential. In this study, we evaluated the effectiveness of formoterol (FOR), a β2-adrenoceptor agonist, in managing muscle wasting caused by DOX. Methods and Results: To evaluate the effect of FOR on DOX-induced muscle wasting, mice were treated with DOX (2.5 mg/kg b.w., i.p. administration, twice a week), associated or not to FOR treatment (1 mg/kg b.w., s.c. administration, daily). Control mice received vehicle solution. Combination of FOR treatment with DOX protected against the loss of body weight (p<0.05), muscle mass (p<0.001), and grip force (p<0.001) promoted by chemotherapy. FOR also attenuated muscle wasting (p<0.01) in tumor-bearing mice on chemotherapy. The potential mechanism by which FOR prevented further DOX-induced muscle wasting occurred by regulating Akt/FoxO3a signaling and gene expression of atrogenes in skeletal muscle. Conclusions: Collectively, our results suggest that FOR can be used as a pharmacological strategy for managing muscle wasting induced by DOX. This study provides new 2 This is a provisional file, not the final typeset article insights into the potential therapeutic use of FOR to improve the overall well-being of cancer patients undergoing DOX chemotherapy.